STUDI HISTORIOGRAFI: KONSEPSI BUNG KARNO TERHADAP STATUS SOSIAL DAN PERANAN WANITA DALAM BUKU SARINAH - Yuda Ariwinata; Hendra Naldi (Department of History Education, Faculty of Social Science, Universitas Negeri Medan, 2023)
This study examines the Sarinah Book by Ir. Soekarno in a historiographical review entitled Sarinah: Women's Obligations in the Struggle of the Republic of Indonesia to see the social status and role of women in Bung Karno's conception. The problems raised in this study are formulated in two formulations (1) How did Bung Karno's background and zeitgeist influence in writing Sarinah's book (2) What were the social status and role of women in Bung Karno's depiction in Sarinah's book. The author uses library research methods which are classified as qualitative research. The steps of this research are as follows. First, find and collect research sources consisting of Sarinah books published in the Old Order period. And relevant work or similar. In collecting research sources, there are three interrelated stages. (1), the researcher prepares research tools and equipment. (2), the researcher arranges work steps. (3), reads and makes notes on the reading. Second, analysis and interpretation, and classification based on the categories that have been compiled by researchers. Third, presenting the data that has been researched in a work in the form of a thesis. The result of the research is that the position of women in a country is very important. men and women must synergize for a progressive movement. women in Indonesia must walk side by side with men in the struggle and efforts to fill Indonesia's independence. The struggle was carried out first to gain independence and second to play an active role in eliminating all forms of colonialism in the forms of imperialism, colonialism, and capitalism. Seta was active in fulfilling independence in striving for the realization of a socialist order in Indonesia.